2023
DOI: 10.1144/jgs2022-175
|View full text |Cite
|
Sign up to set email alerts
|

Concretionary cementation of a Scottish Middle Jurassic sandstone by hot, Paleocene fluids: a clumped isotope study

Abstract: This study focusses on new clumped isotope data from concretionary calcite cements in the Middle Jurassic Valtos Sandstone Formation (Great Estuarine Group) of the Inner Hebrides. Clumped isotopes show that concretion cementation began at 45±6 °C increasing to temperatures in excess of 70 °C before cooling slightly to 57 ± 7 °C at the concretion margin. In the early stages of cementation, calculated δ 18 O FLUID values were ∼ –12‰ VSMOW, identical to an estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…The geology of the concretions, before the clumped isotope work is from Hudson and Andrews (1987) with petrography and geochemistry by Wilkinson (1993), who undertook serial sampling of the concretions. This paper is based on Paxton et al (2023) where detailed discussion of the conclusions summarized here can be found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geology of the concretions, before the clumped isotope work is from Hudson and Andrews (1987) with petrography and geochemistry by Wilkinson (1993), who undertook serial sampling of the concretions. This paper is based on Paxton et al (2023) where detailed discussion of the conclusions summarized here can be found.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical bars indicate the isotopic compositions of Paleocene (lilac) and Jurassic (pale blue) meteoric (rain) water for reference. Image elements adapted from Wilkinson (1993) and Paxton et al (2023).…”
Section: Featurementioning
confidence: 99%